Population risk measurement complementary to the criteria from Amsterdam - Sarroca, Carlos; Della Valle, Adriana; Alfano, Nora; Tedesco, Gladys; Domínguez, Alejandra; Simonet, Fernando; Caracha, Olga (Cirugía del Uruguay, 2000)
With the aim of lowering morbimortality and improving the quality of lite of the increased risk population by early diagnosis of the cancer, we wi/1 demonstrate the validity of new clinical criteria.